ELEVATED MEAN CELL VOLUME IN SICKLE CELL ANAEMIA: ONE STORY, TOO MANY? - Jeremiah, Zaccheaus; Magnus, Alee (Sanamed, 2024)
Introduction: Sickle cell disease is a hereditary blood disorder characterized by defective hemoglobin. Red cell indices are proposed as potential tools for diagnosing and managing sickle cell disorders.Materials and Methods: This study aimed to assess the utility of red cell indices as screening tools for sickle cell anemia. One hundred consenting adults of both sexes participated. Hematological parameters, including packed cell volume, hemoglobin values, hemoglobinelectrophoretic patterns, and red blood cell count, were examined. Mean cell volume (MCV), mean cell hemoglobin concentration (MCHC), and mean cell hemoglobin (MCH) were calculated. Data analysis was performed using GraphPad Prism Software Version 9, with statistical significance set at p < 0.05 (95% confidence interval).Results: Hemoglobin values were significantly lower in SS subjects (5.68 ± 1.7g/dl) compared to AA (11.30 ± 1.5g/dl) and AS groups (11.03 ± 1.4g/dl) (F=32.279; p < 0.00001). The pattern was consistent with PCV and RBC values. Among the red blood cell indices assessed, only MCV showed a significant elevation (95.7 ± 2.4fl) in the HbSS group compared to other groups (F=4.165; p=0.0183). No statistically significant difference was observed in MCHC and MCH values between the three groups (F=0.5373, p > 0.586 for MCHC; F=0.607, p > 0.546 for MCH). The prevalence of hemoglobin variants was as follows: HbAA (77%), HbAS (19%), and HbSS (4%).Conclusion: This study highlights significant reductions in hemoglobin values in SS subjects and a notable elevation in MCV values in the SS blood group. Elevated MCV in sickle cell anemia, where red cells are typically microcytic, warrants further investigation for differential diagnosis.
Keywords: Mean Cell Volume; Sickle Cell Anemia; Hemoglobinopathies; Port Harcourt; Nigeria